Separation of a new triterpenoid saponin together with six known ones from Clematis tangutica (Maxim.) Korsh and evaluation of their cytotoxic activities. Issue 3 (1st February 2023) - Wei, Yangfei; Chen, Tao; Wang, Shuo; Shen, Cheng; Yan, Shuping; Song, Zhibo; Liu, Yarong; Yang, Fengmei; Hai, Ping; Li, Yulin
Abstract: A new triterpenoid saponin, 3- O - β -D-allopyranosyl (1→3)- α -L-rhamnopyranosyl (1→2)- α -L-arabinopyranosyl hederagenin 28- O - α -L-rhamnopyranosyl (1→4)- β -D-glucopyranosyl (1→6)- β -D-glucopyranosyl ester (IV), together with six known ones Hederacholichiside F (I), Tanguticoside B (II), Tauroside St-H1 (III), Hederoside H1 (V), Kalopanaxsaponin G (VI), Hederasaponin B (VII) were separated from Clematis tangutica (Maxim.) Korsh. Their cytotoxic activities were evaluated. Saponins IV (new compound) and I showed selective inhibitory activities against HGC-27 with IC50 values of 20.17 and 66.18 μM. Saponin VII exhibited extensive inhibitory action against HGC-27, Hela and SK-OV-3 with IC50 values of 16.47-71.36 μM. Saponin III showed selective inhibitory activity against SK-OV-3 with the IC50 value of 48.70 μM. All isolated saponins were inactive (IC50 >150 μM) to GES-1. Graphical Abstract: UF0001